Trend of phubbing behavior researches in Indonesian journals: a content-analysis - Yola Eka Putri; Ifdil Ifdil; Berru Amalianita; Linda Fitria (Jurnal Konseling dan Pendidikan, 2024)
The emergence of mobile technology has led to significant transformations in communication. Nevertheless, it has also presented new challenges, notably exemplified by a phenomenon termed as "phubbing," where individuals prioritize their mobile devices over in-person interactions. This analysis of content delves into the research trends surrounding phubbing behavior, focusing specifically on 42 articles regarding phubbing in the Indonesian Journal of Counseling and Psychology within 2018-2024. The data was gathered from the Science and Technology Index (SINTA). Several aspects necessitate examination, such as the publication year, methods, subject or samples, data collection, data analysis, and other discoveries related to phubbing research. This analysis showed a growing interest in phubbing research in Indonesia, characterized by a notable rise in publications over the past 6 years. Furthermore, quantitative methodologies and surveys using questionnaires are becoming prevalent in phubbing research in Indonesia. Another significant point is the prevalence of students as the primary subjects of research, with regression and correlation techniques being the most commonly employed methods of data analysis. Consequently, it can be inferred that further exploration is crucial in phubbing research, incorporating advancements in research topics, participants, data collection methods, and data analysis techniques. The results of this investigation underscore the significance of continued exploration of phubbing, particularly through interdisciplinary approaches, to develop comprehensive strategies in mitigating its negative impacts. This study provides valuable insights for researchers and professionals seeking to comprehend and tackle the phubbing phenomenon in Indonesia.